AB1069 Shoulder ultrasonography in diabetic patients – is there damage with no clinical sign?. (15th June 2017) - Iorgoveanu, VC; Bojinca, V; Malitchi, R; Gheorghe, M; Ionescu, C; Ionescu, R
Abstract : Background: Degenerative lesions in shoulder rises exponentialy with age and diabetes was found to be associated with shoulder pain [1, 2]. Objectives: To evaluate the prevalence and type of lesions of shoulder in diabetic patients with no pain using ultrasound (US). Methods: We included consecutive patients with diabetes with no pain or clinical tumefaction in shoulder. US was performed in both shoulders using the standard scanning planes and dynamic maneuvers. Clinical data as fasting glycemia, BMI, treatment were recorded. Results: Forty two shoulders were examined in 21 consecutive patients (mean age 67.92+/-7.35 years, weight 81.75 +/- 13.57 kg, BMI 25+/-2 kg/m 2, fasting glycemia 151.85+/-33.72mg/dl) with diabetes diagnosis mean 5.33 years +/- 5.99. Majority of patients were under treatment with oral antidiabetics (58.3%). Degenerative lesions were found in subscapular (SSc) 33.3% and supraspinatus (SpS) 8.3%) tendons as well as intratendinous micro ruptures with calcifications (33.3% bilateral calcifications in SSc, SpS). Impingement syndrome was objectified in 16.6% of examinations. Minimal inflammatory signs as: sub-acromion sub deltoidian bursitis in 50% (minimum in 33.3%, 8.3% bilateral) and long head biceps tenosynovitis in 58.33% (8.3% minimal Doppler signal). 83.3% showed humeral irregularities and also erosions were found (8.3%). Conclusions: Degenerative and minimal inflammatory lesions in shoulder of diabetic patients exist with no clinical sign (pain, tumefaction). Ultrasonography might be an usefull technique to confirm these alterations before the appearance of symptoms. References: Thomas SJ, McDougall C, Brown ID, et al. Prevalence of symptoms and signs of shoulder problems in people with diabetes mellitus. J Shoulder Elbow Surg. 2007;16:748–751. Abate M, Schiavone C, Salini V. Sonographic evaluation of the shoulder in asymptomatic elderly subjects with diabetes. BMC Musculoskelet Disord. 2010;11:278. Disclosure of Interest: None declared